Larvicidal activity of Cestrum nocturnum on Aedes aegypti - Chetan Jawale, Rambhau Kirdak, Laxmikant Dama (Bangladesh Pharmacological Society, 2010)
Aedes aegypti is a vector parasite of the Dengue. New method to control the population of this insect is necessary. In the present work we evaluated the potential of extract from Cestrum nocturnum as larvicide. Methanol extract outstand as highly active larvicide, achieving 100 % larval mortality in 24 hours when tested in the concentration of 45 µg/mL (soxhlet) and 25 µg/mL (percolation). Any extract exhibiting significant larvicide activity was further fractioned and the fraction tested according to the WHO protocol. One fraction derived from methanol extract present remarkable LC100 at 12 µg/mL. LC50 of methanol extract and active fraction were found 14 µg/mL and 6 µg/mL respectively. These fractions will be submitted to further fractions aiming to identify the molecules responsible for the larvicide activity.